PERAN MANAJERIAL KEPALA SEKOLAH DALAM PENGADAAN PROGRAM KEAHLIAN SISWA - Eko Budiywono; Muh Nahnu Najamuddin (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
This research is aimed at: 1) Knowing the role of managerial principals in the procurement of vocational skills programs for SMK Darussalam Blokagung students. 2) find out what efforts are being made in the procurement of vocational student expertise programs Darussalam Blokagung. 3) Knowing the supporting and inhibiting factors of managerial implementation principals in an effort to procure the Darussalam Vocational High School student expertise program. As for the method in this study uses qualitative research, and the data collection carried out by the method of observation, documentation. and all interviews carried out to answer problems regarding the principal's managerial procurement of skills programs for Darussalam Vocational High School students. Based on the results of research that has been obtained in the field, it shows that 1) The main role of the principal as an educational leader is to create learning situations so that a teacher can teach his students and students can study well. 2) the efforts made in the procurement of expertise programs namely the principal as a manager must be able to manage so that all the potential of the school can function and run optimally. This can be done if the principal able to carry out management functions well, including: Planning organizing, directing/controlling, and supervising. 3) supporting factors and obstacles in the procurement of expertise programs in carrying out these roles, namely: all teachers and employees feel involved starting from planning, organizing, implementation, and evaluation. of school programs in their procurement and determination, then the principal is expected to have good leadership skills is one of the factors that can affect the quality of education, carry out school administration so as to create a good learning situation.